Integration of Technology and Art through Smartphone Photography Classes for Community Empowerment - Samosir, Irniyati; Sudrajat, Jajat; Wahyudin, Uyu; Sardin, Sardin; Shantini, Yanti (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aimed to investigate the integration of technology and art in community-based nonformal education through smartphone photography classes, with the objectives of (1) strengthening digital skills, (2) fostering creative expression, (3) enhancing visual literacy, and (4) opening economic opportunities for participants. This study specifically explores how photography training using mobile devices can function as a means of empowerment in community education. Method: A qualitative descriptive approach was employed, focusing on Kleas Moto Teh Ina, an online photography training community utilising mobile devices. Data were collected through document analysis, participant observation, and in-depth interviews, and thematic analysis was conducted to identify key trends, dynamics, and program impacts. Results: The results demonstrate that participants (1) significantly improved their technical photography skills, particularly in lighting, composition, and photo editing, (2) alongside advancements in digital literacy and self-confidence, and (3) many participants translated these skills into creative economic activities, including professional content creation and promotion of micro, small, and medium enterprises (MSMEs). Novelty: The novelty of this study lies in presenting smartphone-based photography education as a sustainable and inclusive empowerment model. It contributes to bridging digital literacy gaps while offering a pragmatic and innovative approach to community learning in the digital age.